Macro and Micro Anatomical Comparative Study for Liver, Kidney and Testis Between the Albino Rat and Pigeon - Alnassiri, Shurooq Hameed Majeed (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
The present study was designed to demonstrate the anatomical and histological variations between the certain organs in both the rat as a model of experimental mammals and pigeon as an avian model. Five albino rats and five pigeons were utilized, the liver, kidney and the testicles were taken from those animals after scarifying and specimens were taken from those organs, fixed in 10 % formalin for 24 hours before transferred for histological technique, the slices were stained with hematoxylin and eosin. The anatomical observation indicated that the liver of rat was formed by right, left lobes and intermediate, located in the anterior part of abdomen, in the pigeon, had two lobes without gall bladder. The kidney of the rat was bean shaped, brown reddish color with idented medial border present in the abdominal cavity near and around the lumbar vertebrae, the kidney of pigeon was lobulated into three and the kidney was lodged on the ventral aspect of the synsacrum. The testis of rat was oval in shape present in the scrotum, and in the pigeon located in the abdominal and pelvic cavity. The histological result indicated the liver of rat was with columns of polygonal liver cells surrounded by blood sinusoids draining in the central vein, while in the pigeon, the cells were present in groups also had blood sinusoids with Kupffer cells and central vein for draining the blood outside the liver, the kidney of both types had an cortex and medulla with presence of glomeruli in the cortex, both had proximal and distal convoluted tubules , in the pigeon there is no thin segment of Henle loops . The testis was occupied by seminiferous tubules in both types and each tubule was containing the different types of spermatic cells and spermatozoa, also Leydig cells were present in groups, spermatogenesis was intensive in pigeon in cases of seasonal phase in conclusion, variation for the visceral organs in both rats and pigeon were determined also histological differences were present, otherwise similarities were also observed.